(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The water and environment has become an emotive issue for the people and policy makers. The chief causes for the pollution of water and environment are anthropogenic activities of human beings. Studies of Physico-chemical parameters of water quality based on Physico-chemical paratmeres have been taken from Sonbhadra district, Uttar Pradesh was conducted in pre monsoon season of the year 2022 to evaluate its suitability for domestics purpose. The quality analysis has been made through the pH temperature